THE EFFECT OF SALT TOLERANT NITROGEN FIXING BACTERIA ON THE GROWTH OF PADDY RICE (Oryza sativa. L) - Suliasih Suliasih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Nitrogen fixing bacteria (Azospirillum and Azotobacter) were isolated from coastal mangrove in Pulau seribu. The aims of this experiment was to find out isolates of nitrogen fixing bacteria which were tolerant to high salinity. The isolates can be used as a biofertilizer to support coastal agriculture. A total of 28 isolates (14 isolates of Azospirillum and 14 isolates of Azotobacter) were tested their tolerance to salt by growing them in their respective media containing 1% 2% and 3 % NaCl,. Salt tolerant isolates obtained, then used as inoculants in paddy. The experiment laid out factorial based randomized complete block design which was comprised of 7 fertilizer treatments and 5 watering treatments with 5 replicates for each treatment at green house of Microbiology Division, Research Center of Biology, Indonesian Institute of Sciences. The first factor was fertilizer treatments 1. Compost + mixed bacteria (K1), 2. Control without inoculant, 3. Compost, 4. NPK, 5. Compost + NPK + mixed microbial, 6. Azotobacter isolates; 7. Azospirillum isolates. The second factor was watering treatments, plant was watered by : 1. freshwater, 2. freshwater + sea water at mixture ratio 1:1, 3. Sea water, 4. sea water + 2% NaCl (20 g NaCl / l), 5. freshwater + 5% NaCl (50 g NaCl / l). The result showed that there were 9 isolates of Azospirillum and 4 isolates of Azotobacter which were tolerant to grow at media with 3% NaCl. The green house experimental result revealed that the plants were treated with bacteria can survive up to the level of salinity 12.43 dS-1m.